PENENTUAN RASIO-RASIO KEUANGAN YANG BERPENGARUH TERHADAP KESEHATAN KEUANGAN PERUSAHAAN ASURANSI UMUM DI INDONESIA - Andi Indra Martini (Jurnal Mirai Management, 2020)
The results indicated that there was a significant difference between well financial performances of general insurance firms and inappropriate financial performances of general insurance firms. These can be seen at F test, Sig and Wilk’s Lambda. This research also could produced Z Score Model, in which could differentiate the well financial performances and inappropriate financial performances with the level of accuracy of 88%. This research discovered that the ratio that could affect the well financial performances for general insurance firms in Indonesia, are ratios between Net retention premium and equity and ratio between profit (loss) after tax to average equity. This research also shown that the government policy on Finance Minister Decision No.424/KMK 06/2003 and the plan provided on Indonesian Insurance Architect, would be able to improve financial performances of general insurance firms.